Pembungkaman Narasi dan Suara Palestina Pasca Eskalasi Perang Israel-Palestina 2023 - Muhamad Aufal Ghufron (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2026)
The Israel–Palestine conflict is one of the world’s longest-running disputes and has escalated again following Hamas’s attack on October 7, 2023. Beyond the military arena, this conflict also raises issues of freedom of expression and the silencing of Palestinian writers internationally. This study employs a qualitative-descriptive approach to examine Palestinian literature as a space for articulating identity, resistance, and collective memory amid the Israel–Palestine conflict. This method enables the researcher to deeply interpret the social, political, and cultural dynamics reflected in literary texts and practices, as well as to trace systematic efforts to silence and marginalize Palestinian narratives on the global stage. The study analyzes three cancellation cases that represent patterns of silencing Palestinian narratives in cultural and academic spheres: Adania Shibli at the Frankfurt Book Fair (2023), Mohammed El-Kurd’s lecture at the University of Vermont (2023), and Randa Abdel-Fattah’s invitation at Adelaide Writers’ Week (2026). Three main silencing patterns are identified: legitimizing censorship for security reasons, political dominance in cultural/academic institutions, and transnational solidarity as a form of resistance. These practices reveal the vulnerability of the Palestinian narrative within global structures, yet also trigger collective resistance and international solidarity.Keywords - Israel-Palestine Conflict, Palestinian Voice, Palestinian Writers.